Effects of object size and distance on reaching kinematics in patients with schizophrenia - Shu-Mei Wang; Li-Chieh Kuo; Wen-Chen Ouyang; Hsiao-Man Hsu; Hui-Ing Ma (SAGE Publishing, 2018)
Background/Objective Patients with schizophrenia not only have psychiatric symptoms, but also have movement problems, which might also be associated with their reduced quality of life. Little is known about how to improve their movement performance for patients. Manipulating object size and distance is common in occupational therapy practice to evaluate and optimize reaching performance in patients with physical disabilities, but effects of the manipulation in patients with schizophrenia remain unclear. The purpose of this study was to examine whether object size and distance could change performance of reaching kinematics in patients with mild schizophrenia. Methods Twenty-nine patients with mild schizophrenia and 15 age- and gender-matched healthy controls were required to reach for, as quickly as possible, a small or large object that was placed at a near or far distance. We measured movement time, peak velocity, path length ratio, percentage of time to peak velocity, and movement units to infer movement speed, forcefulness, spatial efficiency (directness), control strategies, and smoothness. Results Patients' reaching movements were slower ( p = .017) and less direct ( p  = .007) than those of controls. A larger object induced faster ( p  = .016), more preprogrammed ( p  = .018), and more forceful ( p  = .010) movements in patients. A farther object induced slower, more feedback dependent, but more forceful and more direct movements (all p  < .001). Conclusion The results of kinematic deficiencies suggest the need of movement training for patients with mild schizophrenia. Occupational therapists may grade or adapt reaching activities by changing object size and distance to enhance movement performance in patients with schizophrenia.